Perancangan Penerapan e-Commerce pada UMKM Keripik Singkong HIKMAH - Sania Gusti Rahayu; Rakhmat Ceha; Reni Amaranti (UNISBA Press, 2022)
Abstract. The MSME sector is growing over time, as more people get interested in becoming MSME actors. The number of business actors establishing MSMEs creates competition. Currently, MSME actors are using the internet in their businesses in order to increase revenues. HIKMAH is an MSME that was created in 2011 that manufactures a variety of snacks, including cassava chips in spicy, salty, 'balado', orange, and original flavors. Observations were carried out to understand the ongoing business processes and challenges faced in HIKMAH, namely that the relationship between suppliers and HIKMAH did not operate smoothly in terms of the flow of information and goods, decreased product sales, and decreased marketing activities. There have been no marketing or sales initiatives through digital media. The e-commerce prototype is based on the requirements of 'HIKMAH'. Interviews with the owner were conducted to gain an understanding of the proposed business process. The proposed business process entails increasing system engagement by developing technologies to facilitate 'HIKMAH' interactions with other supply chain actors, including cassava suppliers (raw material procurement operations) and retailers/distributors/consumers (product sales activities). This study generates an e-commerce concept design based on the supply chain process flow, beginning with the process of sourcing raw materials from suppliers to 'HIKMAH' and ending with the sales process to retailers and customers. The design of e-commerce implementation can add value to the movement of products, information and money in the supply chain. Abstrak. Sektor UMKM berkembang dari waktu ke waktu, karena semakin banyak orang yang tertarik untuk menjadi pelaku UMKM. Banyaknya pelaku usaha yang mendirikan UMKM menimbulkan persaingan. Saat ini para pelaku UMKM memanfaatkan internet dalam usahanya untuk meningkatkan pendapatan. HIKMAH merupakan UMKM yang berdiri sejak tahun 2011 yang memproduksi aneka jajanan, antara lain keripik singkong dengan rasa pedas, asin, balado, jeruk dan original. Observasi dilakukan untuk memahami proses bisnis yang sedang berjalan dan tantangan yang dihadapi di HIKMAH, yaitu bahwa hubungan antara pemasok dan HIKMAH tidak berjalan lancar dari segi arus informasi dan barang, penurunan penjualan produk, dan penurunan aktivitas pemasaran. Belum ada inisiatif pemasaran atau penjualan melalui media digital. Prototype e-commerce didasarkan pada persyaratan HIKMAH. Wawancara dengan pemilik dilakukan untuk mendapatkan pemahaman tentang proses bisnis yang diusulkan. Proses bisnis yang diusulkan memerlukan peningkatan keterlibatan sistem dengan mengembangkan teknologi untuk memfasilitasi interaksi 'HIKMAH' dengan pelaku rantai pasokan lainnya, termasuk pemasok singkong (operasi pengadaan bahan baku) dan pengecer/distributor/konsumen (kegiatan penjualan produk). Penelitian ini menghasilkan rancangan konsep e-commerce berdasarkan alur proses rantai pasok, dimulai dengan proses pengadaan bahan baku dari pemasok ke HIKMAH dan diakhiri dengan proses penjualan ke pengecer dan pelanggan. Rancangan implementasi e-commerce dapat menambah nilai pergerakan produk, informasi dan uang dalam rantai pasok.